How do I implement a whole blood–based blood preparedness program in a small rural hospital?. Issue 12 (12th September 2020) - Apelseth, Torunn O.; Strandenes, Geir; Kristoffersen, Einar K.; Hagen, Kristin G.; Braathen, Hanne; Hervig, Tor
Abstract: Civilian and military guidelines recommend balanced transfusion to patients with life‐threatening bleeding. Early start of transfusion has shown improved survival. Thus, a balanced blood inventory must be available in all levels of health care to ensure early stabilization and damage control resuscitation of patients with bleeding. Whole blood has been reintroduced as a blood product for massive bleeding situations because it affords plasma, red blood cells, and platelets in a balanced ratio in a logistically advantageous way. In this article, we describe how to establish a whole blood–based blood preparedness program in a small rural hospital with limited resources. We present an implementation tool kit, which includes discussions on whole blood program strategies and the process of developing detailed procedures on donor selection, collection, storage, and transfusion management of whole blood. The importance of training and audit of the routines is highlighted, and establishment of an emergency walking blood bank is discussed. We conclude that implementation of a whole blood program is achievable in small rural hospitals and recommend that rural health care facilities at all treatment levels enable early balanced transfusion for patients with life‐threatening bleeding by establishing protocols for whole blood–based preparedness.